Human Resource Management Practices and Firms Performance in Bangladesh: An Empirical Study on Pharmaceutical Industry - Aktar, Serena; Islam, Md. Shoriful; Hossen, Sayed Mohibul (Asian Business Review, 2012)
This research work has been conducted in the field of human resource management (HRM), more specifically on firm performance. The aim of the study is to show the relationship between HRM practices and firms performance of pharmaceutical industry in Bangladesh. It is assumed that HRM practices could positively influence profitability and growth and depressingly bias employee turnover. The primary data were collected using structured questionnaire sent to employees of different departments having different job status of some pharmaceutical companies in Bangladesh. Secondary data were collected from annual reports of the selected companies for measuring and finding out their performance. The paper has tried to elucidate the role of HRM practices and to test the relationship among the variables indicating that HRD has a relationship with performance like inventory turnover, total assets turnover, net profit margin, gross profit margin etc. It is found that HRM practices enhance performance of the pharmaceutical firms in Bangladesh.